MULTI-STAGE MIXING IN SUBDUCTION ZONES: APPLICATION TO MERAPI VOLCANO (JAVA ISLAND, SUNDA ARC) - Debaille V.; Doucelance R.; Weis D.; Schiano P. (My University, 2006)
Many studies have argued for the contribution of at least three components, namely the mantle wedge, the subducted oceanic crust, and its sediment cover, to describe the geochemistry of island arc volcanics. However, isotope correlations reflecting a simple binary mixing can be observed at the scale of a single arc island or volcano. Here we investigate the possibility that these trends reflect pseudo-binary mixing relationships in a three-component system. We present a simplified, two-stage model for the systematic isotope modelling of a cogenetic suite of arc lavas. This includes metasomatism of portions of the mantle wedge by hydrous phases released from the down-going oceanic crust, and sediments, followed by progressive mixing and melting. A consequence of this model is that it leads to a two end-member mixing process from the mantle wedge, oceanic crust, and sediment components. To solve the model we reduce it to a step-by-step procedure combined with a Monte-Carlo simulation. The procedure consists of: (i) producing a large number of random values on each variable of the model; (ii) using the computed values to calculate the isotopic compositions of lavas; and (iii) comparing the obtained isotopic compositions with measured data. Applied to a new set of Sr, Nd, and Pb isotope data for volcanics (basalts, basaltic andesites, trachybasalts, and basaltic trachyandesites) from Merapi volcano (Java island, Sunda arc), the model successfully reproduces the binary mixing relationships previously documented for the medium-K and high-K lava series from this volcano, thus giving further support to the hypothesis that this distinction is inherited from the primary magmas and primarily reflects a property of the mantle source. The results allow identification of a set of numerical values for bulk partition coefficients (solid/hydrous fluid, and solid/H2O-rich melt) and variables (e.g., the mass ratio between the metasomatizing phase and the mantle wedge), which can be used for quantitative arc-lava petrogenetic calculations. They also require a direct relationship between dehydration of the slab and melting of the metasomatized mantle wedge. Finally, our evaluation shows that for isotope modelling of the Merapi lavas, the two-stage procedure is controlled more by the considered source components (mantle wedge, oceanic crust, sediments, and their derivatives) than by the various processes involved (dehydration, melting, and mixing). ? 2005 Elsevier Inc. All rights reserved.
Keywords: CRUSTAL RECYCLING; MAGMA CHEMISTRY; SUBDUCTION ZONE; ASIA; GREATER SUNDA ISLANDS; JAVA